(untitled) (New York, NY, 1986)
Industrial Robotics encompasses the entire spectrum of the state of the art. It provides a unique, interdisciplinary treatment of robotics-showing the contributions of the various fields of mechanical, electrical, and industrial engineering, and computer science, to robotics. The authors bring it all together from design to use. And there is no shirking from peripheral activities such as CAD-CAM and artificial intelligence.
Keywords: Robots, industrial